2002
DOI: 10.1128/iai.70.11.6206-6214.2002
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Regulators of Complement Activation byStreptococcus pyogenesSerotype M1

Abstract: Opsonization of bacteria by complement proteins is an important component of the immune response. The pathogenic bacterium Streptococcus pyogenes has evolved multiple mechanisms for the evasion of complementmediated opsonization. One mechanism involves the binding of human regulators of complement activation such as factor H (FH) and FH-like protein 1 (FHL-1). Acquisition of these regulatory proteins can limit deposition of the opsonin C3b on bacteria, thus decreasing the pathogen's susceptibility to phagocyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
82
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(91 citation statements)
references
References 52 publications
4
82
1
2
Order By: Relevance
“…This result suggests that serum proteins other than complement compo- nents are needed to cleave C3b to iC3b. We hypothesized that the serum complement regulatory proteins factor H and factor I could contribute to the cleavage of C3b to iC3b on the S. aureus surface because other gram-positive bacteria, Streptococcus pyogenes and Streptococcus pneumoniae, bind factor H (8,14,15,21,22), a cofactor for factor I-mediated cleavage of C3b to iC3b.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result suggests that serum proteins other than complement compo- nents are needed to cleave C3b to iC3b. We hypothesized that the serum complement regulatory proteins factor H and factor I could contribute to the cleavage of C3b to iC3b on the S. aureus surface because other gram-positive bacteria, Streptococcus pyogenes and Streptococcus pneumoniae, bind factor H (8,14,15,21,22), a cofactor for factor I-mediated cleavage of C3b to iC3b.…”
Section: Discussionmentioning
confidence: 99%
“…Factor H can also accelerate the decay of the C3Bb convertase of the alternative complement pathway, resulting in decreased activation of this pathway (reviewed in reference 16). Notably, two other gram-positive bacteria, Streptococcus pyogenes and Streptococcus pneumoniae, are both able to bind complement factor H (8,14,15,21,22). We hypothesized that S. aureus might convert bound C3b to iC3b via similar interactions with factor H and factor I.…”
mentioning
confidence: 99%
“…Heat-inactivated bacteria were prepared from overnight cultures and grown in Todd-Hewitt broth without shaking in 5% CO 2 at 37°C. The bacteria were harvested, washed, and resuspended in PBS containing 10 g/ml protease inhibitor E64 to 10 10 bacteria/ml (23). The bacterial suspension was incubated at 90°C for 14 min, washed, and resuspended in PBS supplemented with E64.…”
Section: Bacteriamentioning
confidence: 99%
“…Several pathogenic microorganisms express surface proteins capable of interacting with factor H and FHL-1, such as the Mand the Fba protein of S. pyogenes (16,27,28), PspC, Hic proteins of pneumococci (20, 29 -31), Por1A protein of nonsialylated N. gonorrhoeae (32), and envelope proteins gp41 and gp120 of the human immunodeficiency virus (33). Our previous studies indicated that moderate or fully complement-resistant B. burgdorferi and Borrelia afzelii strains, but not complementsensitive Borrelia garinii strains, express up to five factor H-and FHL-1-binding surface molecules termed complement regulator-acquiring surface proteins (CRASPs) (13,34,35).…”
mentioning
confidence: 99%